The Development of Codas in Catalan - Pilar Prieto (Universitat Autònoma de Barcelona, 2006)
This paper focuses on the development of syllable-final consonants in Catalan. Developmental data by four Catalan-speaking children (Serra-Solé corpus in CHILDES) has revealed that codas appear with the very first word productions. The role of the following factors in the development of coda acquisition has been systematically analyzed: within-word position, stress, morphological import and segmental composition. The paper presents empirical evidence in favor of the privileged status of metrically prominent syllables (or heads and edges of feet) in licensing coda consonants in Catalan: it is clear that stressed syllables make their coda available before unstressed syllables, independently of within-word position or morphological import. Similarly, word-final positions are privileged and codas in word-final position are acquired earlier than those in wordmedial position. Our results also contribute to the discussion about the potential facilitating effect of morphology in phonological acquisition. While Freitas, Miguel & Hub Faria (2001) find evidence for an early emergence of plural markers (expressed as word-final coda fricative [-ʃ]) in European Portuguese, Lleó (2003) reports late acquisition of plural markers (word-final coda fricative [–s]) in Spanish. The Catalan data, like the Spanish data, show that morphological codas are acquired relatively late.